(3UhQI cJGH UGOQ ef GdSdWGf SdjeGf Hf GdSdWGf Sdje SfI (B958(3g`s
(3ChdgG (B:s
(3gPG eKGdfG GdSGei GdSdWGfi hNWGHfG Gdefja GdYGdi GdNGbGfi s
(3BNQgG (B:s
(3hYdGeJfG GdTQjag MLI Ydjg hGdSdGe Ydjg , hdGMhd hdGbhI EdG HGddg GdYdi GdYXje s
(3hgPG GdcJGH UGOQ Edi GdEeGe GdeWgQ EeGe GdRjOjI HGdjef hLhGH GdeWgQ Ydjgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B266 s
Keywords: (3GdJGQjNs